Why central banks (and money) rule the roost - Claudio Sardoni (Levy Economics Institute of Bard College, 2006)
Some have argued that a significant decrease in the demand for money, due to financial innovations, could imply that central banks are unable to implement effective monetary policies. This paper argues that central banks are always able to influence the economy's interest rates, because their liability is the economy's unit of account. In this sense, central banks rule the roost. In the 1930s, starting from Keynes's ideas and referring to money in general, Kaldor had followed a similar line of analysis. In principle, a new unit of account could displace conventional money and, hence, central banks. But this process meets relevant obstacles, which essentially derive from the externalities and network effects that characterize money. Money is a social relation. Money and central banks are the outcome of complex social and economic processes. Their displacement will occur through equally complex processes, rather than through mere innovation.
Keywords: E41; E42; E52; E58; 330; Money; monetary policy; financial innovation; central banking